Chennai urban land market assessment - David E. Dowall; Paavo Monkkonen (University of California, Institute of Urban and Regional Development (IURD), 2007)
This paper reports on the results of a land market assessment conducted in the Chennai Metropolitan Area in India. It provides detailed spatially disaggregated information on land use, population, and housing and land values for the metropolitan area. The assessment was a joint effort of the World Bank, the Chennai Metropolitan Development Authority (CMDA) and the Department of Geography at the University of Madras. The study was initiated in June 2003, and the underlying methodology and approach is provided by Dowall (1995).1 The CMDA was responsible for compiling detailed archival land-use information for the metropolitan area for 1971, 1981, and 1991. In addition, the CMDA interpreted IKONOS satellite images for 2001. The CMDA also built the socioeconomic and housing database, linking together information on population, households and dwelling units from Government of India Censuses for 1971, 1981, 1991 and 2001. The University of Madras's Department of Geography was responsible for carrying out the extensive surveys of real estate brokers in the metropolitan area. A total of 688 observations were tallied on various types of residential and industrial land prices.
Keywords: 330